Pengembangan Media Pembelajaran Komputer Berbasis Simulasi untuk Materi Menulis Puisi di Kelas X SMK Al-Washliyah - Putri, Nevia Sefiana; Ali, Ali; Rita, Rita (Medan Resource Center, 2024)
This study aims to evaluate the feasibility and effectiveness of computer-based learning media with a simulation model for poetry writing in class X at SMK Al-Washliyah. The research employs a research and development (R&D) approach, encompassing steps such as data collection, planning, product development, initial field trials, revisions, further trials, product refinement, field implementation, final adjustments, and dissemination. The population and sample of the study comprised 30 students. Results indicate the media's high feasibility, with media experts rating it